2018
DOI: 10.1080/13685538.2018.1424130
|View full text |Cite
|
Sign up to set email alerts
|

PI3K pathway and Bcl-2 family. Clinicopathological features in prostate cancer

Abstract: The phosphatidylinositol 3-kinase (PI3K)/AKT/mTOR pathways and Bcl-2 family play a central role in prostate cancer (PC). The aim was to determine influence in the biochemical progression in PC. To evaluate the association between clinic pathological and immunohistochemical variables, Spearman's test was performed. Log-rank test and Kaplan-Meier curves were used for survival comparisons. To explore the correlation of the studied immunohistochemical parameters and the established prognostic variables with bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Interestingly, AKT was also identified in the present study. Indeed up to 49% of PC tumors are thought to have aberrant PI3K signaling, making it the 2nd most frequently altered pathway in PC [6870]. However, PI3K monotherapies for PC are ineffective, most likely due to their lack of specificity and complex signaling feedback mechanisms [68, 69, 7174].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, AKT was also identified in the present study. Indeed up to 49% of PC tumors are thought to have aberrant PI3K signaling, making it the 2nd most frequently altered pathway in PC [6870]. However, PI3K monotherapies for PC are ineffective, most likely due to their lack of specificity and complex signaling feedback mechanisms [68, 69, 7174].…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2, a well-known apoptosis suppressor gene, is involved in the progression of multiple tumors. 22 , 23 Studies have reported that many miRNAs can regulate the expression of Bcl-2 . 24 However, the mechanism through which Bcl-2 participates in SCLC biology under the regulation of miR-216a-5p remained obscure.…”
Section: Discussionmentioning
confidence: 99%
“…It results suggest a role for prostatic expression of PI3K has prognostic markers for PC. Also, PI3K/AKT/mTOR and Bcl-2 family are becoming an important therapeutic target and predictive biomarkers of onset and progression of PCa [20]. The literature study has revealed a set of critical genes, which can provide etiologic clues as to enzalutamideresistant prostate cancer and guide novel therapeutic approaches [21].…”
Section: Introductionmentioning
confidence: 99%